Development of a swimming motion display system for athlete swimmers' training using a wristwatch-style acceleration and gyroscopic sensor device - Nakashima, M.; Ohgi, Y.; Akiyama, E.; Kazami, N. (Procedia Engineering, 2010)
The objective of this study was to develop a swimming motion display system for athlete swimmers' training, which is handier and more intuitive than the three dimensional motion capture systems using underwater cameras. In this paper, system structure, reconstruction method of the swimming motion, experiment on land to examine the accuracy, and the software which reconstructs and displays the swimming motion are described.